Morphological Diversities revealed in Rahimi’s Novel The Patience Stone - Ariwibowo, Syamsuri (Dinamika : Jurnal Sastra dan Budaya, 2018)
This study aims to find out the diversity of morphemes  appearing in every word  in the novel. The problems being solved are  the derivational morphemes expressed in the novel and  the frequency of derivational morphemes that appear in  The Patience Stone by Atiq Rahimi. Hopefully, it could be helpful and  useful for application of derivational morpheme correctly. It can also be the reference for learning the word formation. The research method used to analyze the data  is descriptive design. Data are taken from the novel of The Patience Stone about any words containing derivational morpheme and the technique of data analysis used is classification of every word and tabels of the frequency of derivational morpheme. The finding  indicates that derivational suffix -ly is the most frequent morpheme that appears in the novel.  The derivational suffix -hood and -ship are the least frequency of derivational morpheme. Key Words : Word-formation, Morpheme, Affixes